Accuracy of transthoracic echocardiography in the assessment of proximal aortic diameter in hypertensive patients: comparison with cardiac magnetic resonance. Issue 8 (August 2017) - Leone, Dario; Tosello, Francesco; Faletti, Riccardo; Schivazappa, Giulia; Bruno, Giulia; Avenatti, Eleonora; Ravera, Agnese; Veglio, Franco; Milan, Alberto
Abstract : Background: Accurate and reproducible measurements of proximal thoracic aorta diameters are essential in the diagnosis and follow-up of patients with aortic dilatation, a condition particularly common in hypertensive patients. Aim: to evaluate the accuracy of transthoracic echocardiography (TTE) in comparison with cardiac magnetic resonance (CMR) for the assessment of proximal thoracic aorta diameters in a cohort of hypertensive patients. Methods: A total of 75 essential hypertensive outpatients previously evaluated by TTE and than by CMR were included in the study. We specifically compared the two techniques at the level of sinuses of Valsalva (SoV) and ascending aorta (Asc) diameter. For the TTE images, the inner edge-to-inner edge and leading edge-to-leading edge conventions were compared. Results: TTE and CMR diameters were significantly related (SoV: r 0.931, P < 0.001; Asc: r 0.949, P < 0.001) when the leading edge-to-leading edge convention was used. Mean difference between CMR and TTE diameters was 2.49 ± 2.01 mm at the level of SoV and 1.13 ± 1.77 mm at the level of Asc. Correlation was good also for the TEE diameters measured by inner edge-to-inner edge convention (SoV: r 0.936, P < 0.001; Asc: r 0.947, P < 0.001). Comparing the two approaches in the evaluation of Asc, inner edge-to-inner edge showed a trend to a better correlation with CMR measurements than leading edge-to-leading edge, with a good interobserver and intraobserver agreement. Conclusion: The results of the current study suggest that TTE could be a reliable tool to assess proximal aorta diameters in hypertensive patients.